The Effect of Work Discipline and Work Environment on Employee Performance through Work Motivation as an Intervening Variable Study of Employees of the State Treasury Service Office Scope of Regional Office of Central Java Province - Moh Fahrurrozi; Supriyono; Kertati Sumekar (Formosa Journal of Science and Technology, 2023)
This study aims to analyze the effect of work discipline and work environment on employee performance with work motivation as an intervening variable. The research data uses primary data in the form of a questionnaire. The method of determining the sample using the slovin formula and obtained a sample of 134 respondents. The data analysis used in this study is a structural equation model. The results of this study state that work discipline and work environment have a positive effect on work motivation. The results of this study also state that the work environment and work motivation have a positive effect on employee performance. In addition, work discipline does not affect employee performance.